"Adolescents do not only require ARVs and adherence counseling": A qualitative investigation of health care provider experiences with an HIV youth peer mentoring program in Ndola, Zambia. - Elizabeth A Abrams; Virginia M Burke; Katherine G Merrill; Christiana Frimpong; Sam Miti; Jonathan K Mwansa; Julie A Denison (PLoS ONE)
Introduction Adolescents and young adults (AYAs) living with HIV face unique challenges and have poorer health outcomes than adults with HIV. Project YES! was a youth-led initiative to promote HIV self-management and reduce stigma among AYAs in four Ndola, Zambia clinics. Clinic health care providers (HCPs) were involved in multiple intervention aspects, including serving as expert resources during AYA and caregiver group meetings, facilitating resistance test-based AYA antiretroviral drug changes, meeting with participants referred through a safety protocol, and guiding a subset of participants' physical transition from pediatric to adult clinic settings. This study aimed to understand HCP insights on facilitators and barriers to implementing Project YES! and scaling up a clinic-based, youth-focused program. Methods A trained interviewer conducted ten in-depth interviews with participating HCPs from November-December 2018 and analyzed data, identifying key themes. These themes were examined in terms of two implementation science outcomes-acceptability and feasibility-to inform scalability. Results HCPs found peer mentoring valuable for AYAs with HIV and the bimonthly caregiver meetings beneficial to AYA caregivers. HCPs voiced a desire for more involvement in specific processes related to patient clinical care, such as drug changes. HCPs' experiences with the study safety protocol, including referrals for youth experiences of violence, shifted their views of AYAs and informed their understanding of key issues youth face. Considering this, many HCPs requested more resources to support AYAs' varied needs. HCPs noted limited time and clinic space as implementation barriers but felt the program was valuable overall. Conclusions HCPs concluded youth peer mentoring was highly acceptable and feasible, supporting scale-up of youth-led interventions addressing the multi-faceted needs of AYAs living with HIV. Continued provider involvement in resistance test-based antiretroviral drug changes, considered in the context of health system and clinic policy, would enhance long-term success of the program at scale.